Corrosion prevention method for composite glass flakes

By using composite nanoparticles with composite POSS and polypyrrole in composite glass scale anticorrosion coatings, the problem that existing anticorrosion coatings are difficult to protect metal substrates for a long time in extreme environments is solved, and the efficient anticorrosion performance of the coating is achieved. Long-term stability.

CN119463624APending Publication Date: 2025-02-18徐州金诺迪环保工程有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488262.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing anticorrosion coatings are difficult to last forever in extreme environments, cannot provide continuous protection for metal substrates for a long time, and cannot meet the growing anticorrosion technical requirements.

Method used

Compound nanoparticles with octathiol POSS and polypyrrole were prepared and used in composite glass flake anticorrosion coatings to enhance the conductive, dense and impact resistance of the coating.

Benefits of technology

By enhancing the conductive and denseness of the coating, it can effectively slow down the corrosion process of metal substrates, improve the corrosion resistance of the coating, hardness, adhesion and impact resistance of the coating, and extend the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463624A_ABST
    Figure CN119463624A_ABST
Patent Text Reader

Abstract

The invention discloses a composite glass flake corrosion prevention method in the technical field of corrosion prevention. The composite glass flake corrosion prevention method comprises the following steps: S1, preparing composite nanoparticles; s2, preparing a composite glass flake anticorrosive coating; s3, surface treatment; and S4, surface coating. According to the prepared composite nano particles, the electron transmission efficiency of a coating is improved through strong pi-pi interaction, and corrosion of a metal base material is slowed down. The POSS group reduces the porosity of the coating, and enhances the compactness, corrosion resistance, hardness, adhesive force and impact resistance. The lithium ion intercalation increases the interlayer spacing of molybdenum disulfide, prolongs the invasion path of a corrosive medium, and improves the flexibility, impact resistance and electrochemical corrosion resistance of the coating. The unreacted sulfydryl on the octa-sulfydryl POSS promotes the rapid curing of the coating, promotes the formation of a cross-linked network, promotes the dispersion of composite nanoparticles, improves the interfacial compatibility of glass flakes and resin, improves the parallel arrangement degree of the glass flakes, and further enhances the corrosion resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of corrosion prevention, and in particular relates to a composite glass flake corrosion prevention method. Background Art

[0002] As society's quality standards for industrial facilities, mechanical equipment and building structures continue to improve, metal materials have been widely used in many key fields such as construction, petroleum, aerospace, and pipeline transportation due to their unique physical and chemical properties. However, these metal materials are inevitably threatened by corrosion when working under various environmental conditions. Corrosion not only causes equipment failures, mechanical shutdowns and other problems, but may also cause serious safety accidents and bring huge economic losses. Therefore, the development of high-efficiency anti-corrosion coatings to effectively protect the surface of metal substrates to reduce economic losses has become a hot topic of current research.

[0003] Despite this, existing anti-corrosion coatings often have difficulty in maintaining their effectiveness in extreme environments, and are prone to degradation, blistering, shedding, and aging. They are unable to provide long-term protection for metal substrates and are unable to meet the growing requirements for anti-corrosion technology. Existing anti-corrosion technology has not yet been able to fully adapt to the needs of daily life and industrial development. Therefore, it is extremely important to continue to conduct in-depth research on anti-corrosion materials and develop anti-corrosion methods that can effectively protect metal substrates for a long time. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a composite glass flake anticorrosion method. In order to solve the defects that the existing anticorrosion coatings are often difficult to play a role in an extreme environment and cannot provide continuous protection for the metal substrate for a long time, the present invention prepares composite nanoparticles of octathiols POSS and polypyrrole, and uses them in the composite glass flake anticorrosion coating, so as to effectively prevent the metal substrate from corrosion.

[0005] In order to achieve the above object, the following technical scheme is adopted: The present invention provides a composite glass flake anticorrosion method, comprising the following steps:

[0006] S1. Preparation of composite nanoparticles: Sodium molybdate is added to N-methylpyrrolidone, and then allyl mercaptan is added, and the mixture is reacted at 150-300°C for 12-18 hours. After the reaction is completed, the mixture is filtered with ethanol and deionized water to obtain allyl / molybdenum disulfide nanosheets. Octathiols POSS is then added to toluene and stirred, and an initiator and the allyl / molybdenum disulfide nanosheets are added, and the mixture is reacted at 80-100°C for 3-8 hours. After the reaction is completed, the mixture is filtered, and toluene is evaporated to obtain POSS-based disulfide nanosheets. Molybdenum nanopowder, adding the POSS-based molybdenum disulfide nanopowder into n-hexane to dissolve, stirring at room temperature, then adding 2.0 mol / L lithium diisopropylamide solution under nitrogen environment, reacting for 12-24 hours, standing and stratifying after the reaction, taking the upper clear liquid, adding dibenzoyl peroxide and 2 mol / L dilute hydrochloric acid, stirring fully until dissolved, adding pyrrole monomer, reacting at -5°C for 12-15 hours, then filtering, and washing the filter residue with deionized water to obtain the composite nanoparticles;

[0007] S2: Preparation of composite glass flake anticorrosive coating: The composite glass flake anticorrosive coating comprises component A and component B. Anti-settling agent, pigment and deionized water are added to a grinder and ground at 40-60° C. When the particle size of each component is 30 μm-50 μm, a mixed slurry is obtained. The mixed slurry is added to a high-speed disperser together with water-based epoxy resin emulsion, glass flakes, composite nanoparticles, film-forming agent and thickener for high-speed dispersion to obtain component A. Isocyanate curing agent is used as component B, and component A and component B are stored separately;

[0008] S3. Surface treatment: Use a polishing machine to polish the surface of the metal substrate that needs to be anti-corrosive to remove the rust layer and make the surface of the metal substrate smooth without protrusions;

[0009] S4, surface coating: The A component and the B component are mixed evenly in proportion, and applied on the surface of the metal substrate to be protected from corrosion, so as to form a coating on the surface, and the coating is allowed to stand until it is completely dry, and then cured for 7 days.

[0010] Furthermore, the component A includes the following components in parts by weight: 40-60 parts of waterborne epoxy resin emulsion, 1.5-3 parts of anti-settling agent, 5-15 parts of pigment, 10-20 parts of glass flakes, 5-10 parts of composite nanoparticles, 3-8 parts of film-forming agent, 0.5-1.5 parts of thickener, and 30-50 parts of deionized water.

[0011] Furthermore, the B component comprises the following components in parts by weight: 1-2.5 parts of hexamethylene diisocyanate urea and 2-4 parts of hexamethylene diisocyanate trimer.

[0012] Furthermore, in step S1, the feeding ratio of sodium molybdate, allyl mercaptan and N-methylpyrrolidone is (1-2) g: (3-6) g: (40-60) mL.

[0013] Furthermore, in the step S1, the feed ratio of octamercapto POSS, allyl / molybdenum disulfide nanosheets, initiator, and toluene is (1.5-3) g: (5-10) g: (0.01-0.05) g: (50-80) mL.

[0014] Furthermore, in the step S1, the feeding ratio of POSS-based molybdenum disulfide nanopowder, n-hexane, lithium diisopropylamide solution, dibenzoyl peroxide, dilute hydrochloric acid, and pyrrole monomer is (0.3-0.5) g: (20-50) mL: (3.5-5) mL: (2.5-4.5) g: (20-50) mL: (2-5) mL.

[0015] Furthermore, in step S4, component A and component B are mixed according to a mass percentage of 70-90%:10-30%.

[0016] Furthermore, the thickness of the glass flakes is 1-5 μm, and the size of the glass flakes is 200-300 μm.

[0017] Furthermore, the anti-settling agent is a combination of one or more of organic bentonite, alumina and silicon dioxide.

[0018] Furthermore, the pigment is a combination of one or more of aluminum tripolyphosphate powder, zinc tripolyphosphate powder, red lead powder, iron red powder, and composite iron titanium powder.

[0019] Furthermore, the film-forming agent is one of ethylene glycol butyl ether, propylene glycol phenyl ether, and hexylene glycol butyl ether acetate.

[0020] Furthermore, the thickener is one of a hydroxymethyl cellulose thickener, a polyacrylic acid thickener, and a polyurethane thickener.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention introduces vinyl on the surface of molybdenum disulfide and grafts octathiols POSS, then grafts octathiols POSS on the surface of molybdenum disulfide through thiol-ene free radical addition, then performs lithium ion intercalation on the flaky molybdenum disulfide through lithium diisopropylamide, and then composites with polypyrrole to obtain composite nanoparticles. Since there is a strong π-π interaction between molybdenum disulfide and polypyrrole, not only the conductivity of the coating is enhanced, but also the transmission efficiency of electrons in the coating is improved, which helps to transmit electrons to the coating surface. The synergistic effect of the two enhances the passivation effect of polypyrrole on the metal substrate and the barrier effect of molybdenum disulfide on the corrosive medium, thereby effectively slowing down the corrosion process of the metal substrate;

[0023] (2) The introduction of POSS groups reduces the porosity of the coating and enhances the compactness of the coating. At the same time, due to the chemical stability of the POSS groups, the chemical corrosion resistance of the coating is improved, and the hardness, adhesion and impact resistance of the coating are enhanced, which helps the coating to maintain its integrity when subjected to external impact and reduces the penetration of corrosive media. The low surface energy and dense structure of the coating enhance its resistance to penetration of corrosive media, further enhancing the anti-corrosion performance of the coating;

[0024] (3) Due to the lithium ion intercalation of nanoparticles into flaky molybdenum disulfide, the interlayer spacing of molybdenum disulfide is increased, providing more physical barrier layers for the coating, thereby effectively extending the path for the corrosion medium to invade. The increase in interlayer spacing also enables the MoS2 flakes to have better sliding ability, which helps to improve the flexibility and impact resistance of the coating, reduce the damage to the coating caused by mechanical stress, and thus reduce the risk of corrosion. The increase in interlayer spacing also provides more space for polypyrrole molecules to approach the surface of MoS2, thereby enhancing the π-π interaction between them. Lithium particles are doped between the MoS2 layers, thereby increasing the number of carriers, which helps to improve the electrochemical anti-corrosion performance of the coating.

[0025] (4) The presence of unreacted thiol groups on the octathiol POSS not only promotes the rapid curing of the anti-corrosion coating and helps form a dense cross-linked network, thereby enhancing the overall performance of the coating. It also helps to improve the dispersibility of the composite nanoparticles in the epoxy resin and the interfacial compatibility between the glass flakes and the resin, so that the glass flakes are evenly distributed in the coating, thereby increasing their parallel arrangement in the coating. Due to the "maze effect" of the glass flakes, their high parallelism in the coating effectively prolongs the path for the corrosive medium to reach the metal substrate, thereby further improving the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The water contact angle measurement results of the coatings of various embodiments and comparative examples;

[0027] Figure 2The electrochemical impedance test results of the coatings of various embodiments and comparative examples are shown;

[0028] Figure 3 The following are the test results of the actual drying and surface drying time of the coatings of various embodiments and comparative examples.

[0029] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0032] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0033] Example 1

[0034] A composite glass flake anticorrosion method comprises the following steps:

[0035] S1. Preparation of composite nanoparticles: sodium molybdate is added to N-methylpyrrolidone, and then allyl mercaptan is added, and the mixture is reacted at 300° C. for 18 hours. After the reaction is completed, the mixture is filtered with ethanol and deionized water to obtain allyl / molybdenum disulfide nanosheets, and then octamercapto POSS is added to toluene and stirred, and an initiator and the allyl / molybdenum disulfide nanosheets are added, and the mixture is reacted at 100° C. for 8 hours. After the reaction is completed, the mixture is filtered, and the toluene is evaporated to obtain POSS-based molybdenum disulfide nanopowder. The POSS-based molybdenum disulfide nanopowder is added to n-hexane and dissolved, and stirred at room temperature. Then, 2.0 mol / L lithium diisopropylamide solution is added under nitrogen environment, and the mixture is reacted for 24 hours. After the reaction is completed, the mixture is allowed to stand for stratification, and the supernatant is taken. Dibenzoyl peroxide and 2 mol / L dilute hydrochloric acid are added, and the mixture is fully stirred until dissolved. Then, pyrrole monomer is added, and the mixture is reacted at -5° C. for 15 hours. Then, the mixture is filtered, and the filter residue is washed with deionized water to obtain the composite nanoparticles.

[0036] S2: Preparation of composite glass flake anticorrosive coating: The composite glass flake anticorrosive coating comprises component A and component B. Anti-settling agent, pigment and deionized water are added to a grinder and ground at 60° C. When the particle size of each component is 30 μm-50 μm, a mixed slurry is obtained. The mixed slurry is added to a high-speed disperser together with water-based epoxy resin emulsion, glass flakes, composite nanoparticles, film-forming agent and thickener for high-speed dispersion to obtain component A. Isocyanate curing agent is used as component B, and component A and component B are stored separately;

[0037] S3. Surface treatment: Use a polishing machine to polish the surface of the metal substrate that needs to be anti-corrosive to remove the rust layer and make the surface of the metal substrate smooth without protrusions;

[0038] S4, surface coating: The A component and the B component are mixed evenly in proportion, and applied on the surface of the metal substrate to be protected from corrosion, so as to form a coating on the surface, and the coating is allowed to stand until it is completely dry, and then cured for 7 days.

[0039] The component A comprises the following components in parts by weight: 60 parts of waterborne epoxy resin emulsion, 3 parts of anti-settling agent, 15 parts of pigment, 20 parts of glass flakes, 10 parts of composite nanoparticles, 8 parts of film-forming agent, 1.5 parts of thickener, and 50 parts of deionized water.

[0040] The B component includes the following components in parts by weight: 2.5 parts of hexamethylene diisocyanate urea and 4 parts of hexamethylene diisocyanate trimer.

[0041] In the step S1, the feeding ratio of sodium molybdate, allyl mercaptan and N-methylpyrrolidone is 2 g:6 g:60 mL.

[0042] In the step S1, the feeding ratio of octamercapto POSS, allyl / molybdenum disulfide nanosheets, initiator, and toluene is 3 g:10 g:0.05 g:80 mL.

[0043] In the step S1, the feeding ratio of POSS-based molybdenum disulfide nanopowder, n-hexane, lithium diisopropylamide solution, dibenzoyl peroxide, dilute hydrochloric acid, and pyrrole monomer is 0.5 g: 50 mL: 5 mL: 4.5 g: 50 mL: 5 mL.

[0044] In the step S4, component A and component B are mixed according to a mass percentage of 90%:10%.

[0045] The thickness of the glass flakes is 1-5 μm, and the size of the glass flakes is 200-300 μm.

[0046] The anti-settling agent is organic bentonite, the pigment is a combination of aluminum tripolyphosphate powder and red lead powder in a mass ratio of 1:1, the film-forming agent is ethylene glycol butyl ether, and the thickener is a hydroxymethyl cellulose thickener.

[0047] Example 2

[0048] A composite glass flake anticorrosion method comprises the following steps:

[0049] S1. Preparation of composite nanoparticles: sodium molybdate is added to N-methylpyrrolidone, and then allyl mercaptan is added, and the mixture is reacted at 150° C. for 12 hours. After the reaction is completed, the mixture is filtered with ethanol and deionized water to obtain allyl / molybdenum disulfide nanosheets, and then octamercapto POSS is added to toluene and stirred, and an initiator and the allyl / molybdenum disulfide nanosheets are added, and the mixture is reacted at 80° C. for 3 hours. After the reaction is completed, the mixture is filtered, and the toluene is evaporated to obtain POSS-based molybdenum disulfide nanopowder. The POSS-based molybdenum disulfide nanopowder is added to n-hexane and dissolved, and stirred at room temperature. Then, a 2.0 mol / L lithium diisopropylamide solution is added under a nitrogen environment, and the mixture is reacted for 12 hours. After the reaction is completed, the mixture is allowed to stand for stratification, and the supernatant is taken. Dibenzoyl peroxide and 2 mol / L dilute hydrochloric acid are added, and the mixture is fully stirred until dissolved. Then, pyrrole monomer is added, and the mixture is reacted at -5° C. for 12 hours. Then, the mixture is filtered, and the filter residue is washed with deionized water to obtain the composite nanoparticles.

[0050] S2: Preparation of composite glass flake anticorrosive coating: The composite glass flake anticorrosive coating comprises component A and component B. Anti-settling agent, pigment and deionized water are added to a grinder and ground at 40°C until the particle size of each component is 30 μm-50 μm to obtain a mixed slurry. The mixed slurry is added to a high-speed disperser together with water-based epoxy resin emulsion, glass flakes, composite nanoparticles, film-forming agent and thickener for high-speed dispersion to obtain component A. Isocyanate curing agent is used as component B, and component A and component B are stored separately;

[0051] S3. Surface treatment: Use a polishing machine to polish the surface of the metal substrate that needs to be anti-corrosive to remove the rust layer and make the surface of the metal substrate smooth without protrusions;

[0052] S4, surface coating: The A component and the B component are mixed evenly in proportion, and applied on the surface of the metal substrate to be protected from corrosion, so as to form a coating on the surface, and the coating is allowed to stand until it is completely dry, and then cured for 7 days.

[0053] The component A comprises the following components in parts by weight: 40 parts of waterborne epoxy resin emulsion, 1.5 parts of anti-settling agent, 5 parts of pigment, 10 parts of glass flakes, 5 parts of composite nanoparticles, 3 parts of film-forming agent, 0.5 parts of thickener, and 30 parts of deionized water.

[0054] The B component includes the following components in parts by weight: 1 part of hexamethylene diisocyanate urea and 2 parts of hexamethylene diisocyanate trimer.

[0055] In the step S1, the feeding ratio of sodium molybdate, allyl mercaptan and N-methylpyrrolidone is 1 g:3 g:40 mL.

[0056] In the step S1, the feeding ratio of octamercapto POSS, allyl / molybdenum disulfide nanosheets, initiator, and toluene is 1.5 g: 5 g: 0.01 g: 50 mL.

[0057] In the step S1, the feeding ratio of POSS-based molybdenum disulfide nanopowder, n-hexane, lithium diisopropylamide solution, dibenzoyl peroxide, dilute hydrochloric acid, and pyrrole monomer is 0.3 g: 20 mL: 3.5 mL: 2.5 g: 20 mL: 2 mL.

[0058] In the step S4, component A and component B are mixed according to a mass percentage of 70%:30%.

[0059] The thickness of the glass flakes is 1-5 μm, and the size of the glass flakes is 200-300 μm.

[0060] The anti-settling agent is a combination of organic bentonite and alumina in a mass ratio of 2:1, the pigment is a combination of aluminum tripolyphosphate powder, zinc tripolyphosphate powder and iron red powder in a mass ratio of 4:2:1, the film-forming agent is propylene glycol phenyl ether, and the thickener is a polyacrylic thickener.

[0061] Example 3

[0062] A composite glass flake anticorrosion method comprises the following steps:

[0063] S1. Preparation of composite nanoparticles: sodium molybdate is added to N-methylpyrrolidone, and then allyl mercaptan is added, and the mixture is reacted at 200° C. for 15 hours. After the reaction is completed, the mixture is filtered with ethanol and deionized water to obtain allyl / molybdenum disulfide nanosheets, and then octamercapto POSS is added to toluene and stirred, and an initiator and the allyl / molybdenum disulfide nanosheets are added, and the mixture is reacted at 90° C. for 6 hours. After the reaction is completed, the mixture is filtered, and the toluene is evaporated to obtain POSS-based molybdenum disulfide nanopowder. The POSS-based molybdenum disulfide nanopowder is added to n-hexane and dissolved, and stirred at room temperature. Then, a 2.0 mol / L lithium diisopropylamide solution is added under a nitrogen environment, and the mixture is reacted for 18 hours. After the reaction is completed, the mixture is allowed to stand for stratification, and the supernatant is taken. Dibenzoyl peroxide and 2 mol / L dilute hydrochloric acid are added, and the mixture is fully stirred until dissolved. Then, pyrrole monomer is added, and the mixture is reacted at -5° C. for 14 hours. Then, the mixture is filtered, and the filter residue is washed with deionized water to obtain the composite nanoparticles.

[0064] S2: Preparation of composite glass flake anticorrosive coating: The composite glass flake anticorrosive coating comprises component A and component B. Anti-settling agent, pigment and deionized water are added to a grinder and ground at 50°C until the particle size of each component is 30 μm-50 μm to obtain a mixed slurry. The mixed slurry is added to a high-speed disperser together with water-based epoxy resin emulsion, glass flakes, composite nanoparticles, film-forming agent and thickener for high-speed dispersion to obtain component A. Isocyanate curing agent is used as component B, and component A and component B are stored separately;

[0065] S3. Surface treatment: Use a polishing machine to polish the surface of the metal substrate that needs to be anti-corrosive to remove the rust layer and make the surface of the metal substrate smooth without protrusions;

[0066] S4, surface coating: The A component and the B component are mixed evenly in proportion, and applied on the surface of the metal substrate to be protected from corrosion, so as to form a coating on the surface, and the coating is allowed to stand until it is completely dry, and then cured for 7 days.

[0067] The component A comprises the following components in parts by weight: 50 parts of waterborne epoxy resin emulsion, 2 parts of anti-settling agent, 5-15 parts of pigment, 15 parts of glass flakes, 8 parts of composite nanoparticles, 5 parts of film-forming agent, 1 part of thickener, and 40 parts of deionized water.

[0068] The B component includes the following components in parts by weight: 2 parts of hexamethylene diisocyanate urea and 3 parts of hexamethylene diisocyanate trimer.

[0069] In the step S1, the feeding ratio of sodium molybdate, allyl mercaptan and N-methylpyrrolidone is 1.5 g:4 g:50 mL.

[0070] In the step S1, the feeding ratio of octamercapto POSS, allyl / molybdenum disulfide nanosheets, initiator, and toluene is 2 g: 8 g: 0.03 g: 75 mL.

[0071] In the step S1, the feeding ratio of POSS-based molybdenum disulfide nanopowder, n-hexane, lithium diisopropylamide solution, dibenzoyl peroxide, dilute hydrochloric acid, and pyrrole monomer is 0.4 g: 30 mL: 4.5 mL: 3 g: 40 mL: 4 mL.

[0072] In step S4, component A and component B are mixed according to a mass percentage of 80%:20%.

[0073] The thickness of the glass flakes is 1-5 μm, and the size of the glass flakes is 200-300 μm.

[0074] The anti-settling agent is a combination of organic bentonite, alumina and silica in a mass ratio of 3:1:1; the pigment is a combination of aluminum tripolyphosphate powder, zinc tripolyphosphate powder and composite iron titanium powder in a mass ratio of 2:1:1; the film-forming agent is hexanediol butyl ether acetate; and the thickener is a polyurethane thickener.

[0075] Comparative Example 1

[0076] This comparative example provides a composite glass flake anti-corrosion method, which differs from Example 1 in that component A of the composite glass flake anti-corrosion coating does not contain composite nanoparticles, but is replaced by equal amounts of other raw materials in the composite glass flake anti-corrosion coating, and the remaining components, component contents, and preparation steps are the same as those in Example 1.

[0077] Comparative Example 2

[0078] This comparative example provides a composite glass flake anti-corrosion method, which differs from Example 1 in that the POSS-based molybdenum disulfide nanopowder is not compounded with polypyrrole, that is, the POSS-based molybdenum disulfide nanopowder is directly added as a composite nanoparticle into the composite glass flake anti-corrosion coating, and the remaining components, component contents, and preparation steps are the same as those in Example 1.

[0079] Comparative Example 3

[0080] This comparative example provides a composite glass flake anti-corrosion method, which differs from Example 1 in that lithium ion intercalation is not performed when preparing the composite nanoparticles, that is, no lithium diisopropylamide solution is added, and it is directly compounded with polypyrrole. The remaining components, component contents, and preparation steps are the same as those in Example 1.

[0081] Comparative Example 4

[0082] This comparative example provides a composite glass flake anti-corrosion method, which is different from Example 1 in that octamercapto POSS is not grafted on the surface of molybdenum disulfide, that is, commercially available molybdenum disulfide powder is used instead of POSS-based molybdenum disulfide nanopowder to be composited with polypyrrole, and the remaining components, component contents, and preparation steps are the same as those in Example 1.

[0083] Results Analysis

[0084] Tinplate was used as a metal substrate, and the coatings of various embodiments and comparative examples were applied on the surface of the tinplate using a coating brush. After the coating was dry, it was coated again, and this was repeated 3 times to prepare a sample.

[0085] The water contact measurement was performed on the samples of each embodiment and comparative example using a dynamic contact angle meter. The test temperature was 25°C. Five parallel measurements were performed and the median value was taken. The test results are shown in Figure 1 .

[0086] The samples of each embodiment and comparative example were subjected to electrochemical impedance spectroscopy test, and the corrosion resistance of the coating was characterized using a PGSTAT302N electrochemical workstation. The test electrolyte was a 3.5% mass fraction NaCl solution, and the test frequency range was 10 -2 Hz, test results see Figure 2 .

[0087] According to the standard of GB / T1728-1979, the actual drying and surface drying time of the test samples are tested. The test results are shown in Figure 3 .

[0088] The acid resistance, alkali resistance, salt water resistance and salt spray resistance performance tests of each embodiment and comparative example were carried out, and the results are shown in Table 1.

[0089] The acid resistance test method is as follows: prepare a 5% sulfuric acid solution, soak the sample for 24 hours, and then observe whether there are defects such as discoloration, blistering, and rust.

[0090] The alkali resistance test method is as follows: prepare a 5% sodium hydroxide solution by mass, soak the sample for 24 hours, and then observe whether there are defects such as discoloration, blistering, and rust.

[0091] The salt water resistance test method is as follows: soak the sample in deionized water at a temperature of 24±0.3℃ for 24 hours, take it out, wipe it dry and observe whether there is blistering, rusting, shedding, etc.

[0092] The salt spray resistance test is carried out according to ASTM B117-19 standard using a salt spray accelerated corrosion test chamber.

[0093] Table 1 Acid resistance, alkali resistance, salt water resistance and salt spray resistance of each embodiment and comparative example

[0094]

[0095] pass Figure 1-3 It can be seen from Table 1 that the coating prepared by the present invention has a large water contact angle, which proves that it has good hydrophobicity, and the coating has self-cleaning ability and electrochemical impedance, so the anti-corrosion performance is stronger than that of the comparative example, and the actual drying and surface drying time are shorter than those of the comparative examples, and the acid resistance, alkali resistance, salt water resistance and salt spray resistance test results are excellent. In the acid resistance, alkali resistance and salt water resistance tests, there is no rust, blistering, discoloration or falling off. Therefore, the anti-corrosion method of the present invention is effective and suitable for surface anti-corrosion operations on metal substrates.

[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0097] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A composite glass flake anticorrosion method, characterized in that: The steps include: S1. Preparation of composite nanoparticles: Sodium molybdate is added to N-methylpyrrolidone, and then allyl mercaptan is added, and the mixture is reacted at 150-300°C for 12-18 hours. After the reaction is completed, the mixture is filtered with ethanol and deionized water to obtain allyl / molybdenum disulfide nanosheets. Octathiols POSS is then added to toluene and stirred, and an initiator and the allyl / molybdenum disulfide nanosheets are added, and the mixture is reacted at 80-100°C for 3-8 hours. After the reaction is completed, the mixture is filtered, and toluene is evaporated to obtain POSS-based disulfide nanosheets. Molybdenum nanopowder, adding the POSS-based molybdenum disulfide nanopowder into n-hexane to dissolve, stirring at room temperature, then adding 2.0 mol / L lithium diisopropylamide solution under nitrogen environment, reacting for 12-24 hours, standing and stratifying after the reaction, taking the upper clear liquid, adding dibenzoyl peroxide and 2 mol / L dilute hydrochloric acid, stirring fully until dissolved, adding pyrrole monomer, reacting at -5°C for 12-15 hours, then filtering, and washing the filter residue with deionized water to obtain the composite nanoparticles; S2: Preparation of composite glass flake anticorrosive coating: The composite glass flake anticorrosive coating comprises component A and component B. Anti-settling agent, pigment and deionized water are added to a grinder and ground at 40-60° C. When the particle size of each component is 30 μm-50 μm, a mixed slurry is obtained. The mixed slurry is added to a high-speed disperser together with water-based epoxy resin emulsion, glass flakes, composite nanoparticles, film-forming agent and thickener for high-speed dispersion to obtain component A. Isocyanate curing agent is used as component B, and component A and component B are stored separately; S3. Surface treatment: Use a polishing machine to polish the surface of the metal substrate that needs to be anti-corrosive to remove the rust layer and make the surface of the metal substrate smooth without protrusions; S4, surface coating: The A component and the B component are mixed evenly in proportion, and coated on the surface of the metal substrate to be protected from corrosion, so as to form a coating on the surface, and the coating is allowed to stand until it is completely dry, and then cured for 7 days.

2. A composite glass flake anticorrosion method according to claim 1, characterized in that: The component A comprises the following components in parts by weight: 40-60 parts of water-based epoxy resin emulsion, 1.5-3 parts of anti-settling agent, 5-15 parts of pigment, 10-20 parts of glass flakes, 5-10 parts of composite nanoparticles, 3-8 parts of film-forming agent, 0.5-1.5 parts of thickener, and 30-50 parts of deionized water; the component B comprises the following components in parts by weight: 1-2.5 parts of hexamethylene diisocyanate biurea and 2-4 parts of hexamethylene diisocyanate trimer.

3. A composite glass flake anticorrosion method according to claim 2, characterized in that: In the step S1, the feeding ratio of sodium molybdate, allyl mercaptan and N-methylpyrrolidone is (1-2) g: (3-6) g: (40-60) mL.

4. A composite glass flake anticorrosion method according to claim 3, characterized in that: In the step S1, the feeding ratio of octamercapto POSS, allyl / molybdenum disulfide nanosheets, initiator, and toluene is (1.5-3) g: (5-10) g: (0.01-0.05) g: (50-80) mL.

5. A composite glass flake anticorrosion method according to claim 4, characterized in that: In the step S1, the feeding ratio of POSS-based molybdenum disulfide nanopowder, n-hexane, lithium diisopropylamide solution, dibenzoyl peroxide, dilute hydrochloric acid, and pyrrole monomer is (0.3-0.5) g: (20-50) mL: (3.5-5) mL: (2.5-4.5) g: (20-50) mL: (2-5) mL.

6. A composite glass flake anticorrosion method according to claim 5, characterized in that: In the step S4, component A and component B are mixed according to a mass percentage of 70-90%:10-30%.

7. A composite glass flake anticorrosion method according to claim 6, characterized in that: The thickness of the glass flakes is 1-5 μm, and the size of the glass flakes is 200-300 μm.

8. A composite glass flake anticorrosion method according to claim 7, characterized in that: The anti-settling agent is a combination of one or more of organic bentonite, alumina, and silicon dioxide; the pigment is a combination of one or more of aluminum tripolyphosphate powder, zinc tripolyphosphate powder, red lead powder, iron red powder, and composite iron titanium powder.

9. A composite glass flake anticorrosion method according to claim 8, characterized in that: The film-forming agent is one of ethylene glycol butyl ether, propylene glycol phenyl ether, and hexylene glycol butyl ether acetate.

10. A composite glass flake anticorrosion method according to claim 9, characterized in that: The thickener is one of a hydroxymethyl cellulose thickener, a polyacrylic acid thickener, and a polyurethane thickener.